(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the views of different periods on language development. Four stages of articles on language issues in the Uzbek periodicals, the influence of writing on language, the Latin and Cyrillic alphabets, their advantages and differences are studied